Warmth-based Exclusion Feels More Painful Than Competence-based Exclusion - TAI, Kenneth (Institutional Knowledge at Singapore Management University, 2015)
Social exclusion is painful. Research has hitherto not examined whether the basis of exclusion alters the magnitude of pain felt. This research examines whether exclusion that is perceived to be due to lack of warmth or lack of competence influence the degree of pain. Across three studies, exclusion due to lack of warmth is more painful than exclusion due to lack of competence. In Study 3, malleability beliefs moderate the effects of warmth-based exclusion on pain, such that when warmth is believed to be less malleable, warmth-based exclusion leads to greater pain. These findings contribute to emerging recognition of the primacy of warmth-based judgments over competence judgments in social perceptions.